Guest editorial of the special issue 'human-centric, decentralised, and hyper automated cyber-physical systems' - Khari, Manju; González-Crespo, Rubén; Sharma, Hemlata (Journal of Control and Decision, 2023)
The emergence of affordable communication and computer technologies has brought virtual and physical space closer together in recent years. Cyber-physical systems, which are the outcome of this confluence, have changed the condition of healthcare, medicine, the environment, sustainability, transportation, and energy. Cyber-Physical Systems (CPS) are a synthesis of virtual and physical technologies.
Keywords: cyber-physical systems; physical technologies; Emerging; Scopus(2)